Characterization of the Oral Microbiome in Egyptian Patients with Schizophrenia and Bipolar Disorders - AbdElaal, Khlood Ramadan Ali (AUC Knowledge Fountain, 2026)
This study investigates oral microbiome alterations in Egyptian patients with schizophrenia (SZ, n=55), bipolar disorder (BD, n=57), and healthy controls (n=20; total N=132). 16S rRNA sequencing shows a significant decrease in the alpha-diversity (p< 0.05) shared across SZ and BD, with noticeable beta-diversity patterns (PERMANOVA R2=0.104, p=0.001). Twenty-eight discriminatory taxa were identified, including a decrease in the health-associated Neisseria and an increase in Streptobacillus, along with distinct signatures for each disorder (Lachnospiraceae in BD; Tissierellaceae in SZ). SVM classifiers showed high accuracy (AUC up to 0.978) and superior discrimination between SZ patients and control subjects. PICRUSt2 analysis predicted enrichment of lipid metabolism pathways (e.g., fatty acid β-oxidation). These findings suggest changes in the microbiome associated with psychiatric conditions consistent with proposed oral-brain axis involvement, supporting the idea that the salivary microbiome could serve as a promising non-invasive biomarker, pending further validation in larger studies.